2011
DOI: 10.1002/j.2055-2335.2011.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Timeliness of Alternatives to Post‐Discharge Home Medicines Reviews for High‐Risk Patients

Abstract: Background The period 7 to 10 days following hospital discharge is associated with a significant risk of medication misadventure, especially in high‐risk patients. Aim To investigate whether post‐discharge hospital‐initiated medication review (HIMR) pathways are more timely than the post‐discharge home medicines review (HMR) pathway. Method An implementation study conducted over 9 months in 2008/2009 of patients from 3 South Australian hospitals. A risk stratification instrument was used to identify patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…65,79 Key processes A range of CMR models were evaluated. This included CMRs which involved pharmacist 22,44,53 Findings of qualitative work also supported these referral pathways, with stakeholders highlighting the use of pharmacists, nursing staff and other health providers as sources for CMR referrals. 63,64 Studies also reported CMRs undertaken by an accredited pharmacist working in a medical practice, 10,33,42,45 or as part of an ACAT (n ¼ 2), 23,51 community mental health team (n ¼ 1), 35,63 or palliative care team (n ¼ 1).…”
Section: Participant Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations
“…65,79 Key processes A range of CMR models were evaluated. This included CMRs which involved pharmacist 22,44,53 Findings of qualitative work also supported these referral pathways, with stakeholders highlighting the use of pharmacists, nursing staff and other health providers as sources for CMR referrals. 63,64 Studies also reported CMRs undertaken by an accredited pharmacist working in a medical practice, 10,33,42,45 or as part of an ACAT (n ¼ 2), 23,51 community mental health team (n ¼ 1), 35,63 or palliative care team (n ¼ 1).…”
Section: Participant Characteristicsmentioning
confidence: 97%
“…10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44][46][47][48][49][50][52][53][54][55][56][57][58][59][60][61] Some studies investigated CMR in particular demographic groups including older people (R65 years, n ¼ 10) 24,31,[45][46][47][48]51,[55][56][57] and war veterans, widows and dependents (n ¼ 5). 52,[55]…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients selected by the clinical pharmacists were deemed high risk, in both time periods, for medicine misadventure. 319,320 The accuracy of the MITF has improved, while the timeliness decreased from 100% in 2009 to 93% in 2014. Of the five MITF's which were outside the 48 hours, all were sent within 7 days' post-discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, new funding is expected to be available for hospital pharmacists, GP's and community pharmacists to deliver a comprehensive medicines discharge process, including a Hospital Initiated Home Medicines Review. 319 Developing the relationships between community pharmacists, hospital pharmacists, medical practitioners, health clinic staff and engaging patients, will be critical success factors.…”
Section: Discussionmentioning
confidence: 99%